Globalization, Migration, Citizenship, and Sport Celebrity: Locating Lydia Ko between and beyond New Zealand and South Korea. Issue 7 (24th May 2019) - Chang, Ik Young; Jackson, Steve; Tak, Minhyeok
Abstract: The contested terrain surrounding globalization, migration, citizenship, and national identity shape the context in which modern sport celebrity develops in Asia. Focusing on female golf phenomenon Lydia Ko, the analysis locates her celebrity and national identity between her place of birth – Korea – and her place of citizenship – New Zealand. Several intersecting factors influenced Ko's celebrity and identity construction including changes in New Zealand immigration policy, changes in Korean state policy towards overseas nationals, negatively viewed attitudes and behaviours of previous foreign-born celebrities of Korean-descent, and Ko's own public proclamations regarding her national identity.